Perancangan Sistem Informasi Pelayanan Nasabah Berbasis Web Mobile Pada Agen BriLink Cuan Komunika Garut - Astuti, Widya Astuti; Budiman, Tedi; Rosmini, Rosmini (Ma'soem University, 2025)
BRILink Cuan Komunika Garut is one of the service extensions of Bank Rakyat Indonesia that facilitates financial transactions for the community. However, the current manual customer service system creates several issues, such as disorganized queues, delays in cash deposits, and inefficiency in cash withdrawals. This study aims to design a web-mobile-based customer service information system capable of managing digital queue numbers to ensure more orderly, faster, and flexible services. The research method applies a software engineering approach using the Waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. Data collection techniques were carried out through observation, interviews, and analysis of existing systems. The system was developed using HTML, PHP, and MySQL as the database, supported by the jQuery Mobile framework for responsive interfaces across mobile devices. System testing was conducted using the black-box testing method to verify that all functions operate according to user requirements. The results indicate that the proposed system improves service effectiveness, reduces potential conflicts caused by manual queues, and provides a better user experience in accessing BRILink services.